Tik Tok Users' Opinions About Da’wah Religious ModerationIn Tik Tok Conversation - Rakatiwi, Yolanda; Halwati, Umi; Nawawi, Nawawi (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research was conducted to describe the views of influential people in Tk Tok conversations around religious moderation. The ideas and subjects expressed by Mega influencers, Macro influencers, and Nano influencers are examined in this research using public opinion, the agenda-forming model, and the spiral of silence. This research methodology uses qualitative descriptive content analysis techniques. The keyword